A Weighted Discrete Universality Theorem for Periodic Zeta-Functions. II - Macaitienė, Renata; Stoncelis, Mindaugas; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2017)
In the paper, a weighted theorem on the approximation of a wide class of analytic functions by shifts ζ(s + ikαh; a), k ∈ N, 0 < α < 1, and h > 0, of the periodic zeta-function ζ(s; a) with multiplicative periodic sequence a, is obtained.